Human flexibility and arterial stiffness - Kenta Yamamoto (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Most Japanese people have had their flexibility tested in childhood physical education classes. Recent studies may provide a retrospective answer as to why those measurements may be important. Flexibility is one of the components of physical fitness along with cardiorespiratory fitness and muscular strength. Although flexibility was originally assumed to correlate with other aspects of physical fitness, recent studies demonstrate that a less flexible body indicates arterial stiffening. Arterial stiffness has been identified as an independent risk factor for mortality and cardiovascular disorders. Therefore, there is a possibility that flexibility is a novel fitness indicator related to cardiovascular disease, which can be easily evaluated over all ages and in any area (e.g., medical check-up). Now, flexibility may no longer be simply viewed as important just for optimizing functional movement in daily life and/or reducing the risk of injury. This article reviews the recent findings on the relationship between flexibility and arterial stiffness, emphasizing "flexibility and arterial stiffness", "genetics and flexibility", "stretching and arterial stiffness", and "flexibility and blood pressure".